A proposed descriptive metadata schema for the admission and discharge form of the patient health record - Opina, Lean John A.; Punzalan, Ricardo L. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2006)
Data collection has been a relevant facet of research and development. The generation of electronic resources became available in cheaper and more convenient means as the manner of collecting and processing data evolved with technology. However, the demand for accurate and comprehensive data recovery and retrieval intensified due to the inconceivable growth of electronic resources. The situation is evident in many institutions. For hospitals, in particular, this is manifested in the efforts to incorporate electronic media in order to minimize expenses in the generation, maintenance and storage of numerous paper-based records. With this in mind, it is relevant to observe current data collection trends and record keeping practices to come up with means that would facilitate resource discovery.
This research presents the admission and discharge form, in general, and the data elements that comprise the record. Admission and discharge forms of secondary and tertiary government hospitals in Manila and Quezon City are used and analyzed by describing each element depending on field names, data types, input masks, and value ranges structured in each form.
Analysis of the forms revealed that the data elements of the admission and discharge form can be grouped primarily into two sets, the enlistment related data and the admission related data. Both are composed of closely associated data elements. Enlistment related data refers to information gathered at an individual's first encounter with a healthcare provider. On the other hand, admission related data include elements that concern a specific health case.
Several inconsistencies were observed on the use and specification of enlistment and admission related data: (1) continuous or terminal numbering system as unique identifiers, (2) application of coding schemes such as ICD, and, (3) specified value ranges, data format and level of extensiveness.
Using the data gathered and taking into consideration the observed inconsistencies, the researcher identified 12 elements which comparatively describe the form and collectively comprising the descriptive metadata schema. The elements record number, name, birth date, and gender are associated with the record's subject which facilitates patient identification. Principal diagnosis, practitioner, result, and disposition elements all relate to the content or information found in the record regarding the health case. And the remaining source, creator, media and creation date elements all contain information about the creation of the record. The descriptive metadata schema developed will facilitate resource discovery and increase accuracy in resource retrieval.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Medical records -- Philippines -- Data processing; Metadatabases